Preparation method of oxygen-enriched vacancy trimetallic layered hydroxide and application thereof in detection of creatinine
Patent Information
- Application Number
- CN202611152116.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-31
AI Technical Summary
Existing LDH nanozymes have problems in creatinine colorimetric detection, including insufficient regulation of metal components, limited effective introduction of amino acids, inadequate construction of oxygen vacancies, and insufficient ability to maintain peroxidase-like activity under weakly acidic to near-neutral conditions.
By introducing La components, serine, and PVP into the Ni-Mn layered hydroxide system, multi-component synergistic regulation is achieved to regulate the hydrolysis, nucleation, and lamellar growth processes of metal ions, thereby constructing oxygen-vacancy-rich trimetallic layered hydroxide materials.
The catalytic activity and stability of the material were improved under weakly acidic to near-neutral conditions, enabling sensitive colorimetric detection of creatinine with a detection limit of 0.68 μM. It also exhibits a wide pH range and good catalytic performance.
Smart Images

Figure CN122685140B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials and biosensing technology, specifically relating to a method for preparing an oxygen-vacancy-rich trimetallic layered hydroxide and its application in creatinine detection. Background Technology
[0002] Creatinine is an important small-molecule metabolite produced by the metabolism of creatine in the body. It is mainly filtered by the glomeruli and excreted in urine. Its levels in biological samples such as blood and urine are closely related to renal function. Therefore, creatinine testing is of great significance in renal function assessment, chronic kidney disease monitoring, and auxiliary diagnosis of related diseases. Establishing a rapid, sensitive, and easy-to-operate method for creatinine testing has practical application value for early screening and health management of kidney-related diseases.
[0003] Existing methods for creatinine detection mainly include the Jaffe method, enzymatic methods, chromatographic methods, electrochemical methods, and colorimetric methods. Among them, the Jaffe method is based on the colorimetric reaction of creatinine with picric acid under alkaline conditions. It is relatively simple to operate, but is easily interfered with by coexisting substances such as glucose, protein, ketone bodies, and ascorbic acid, and its selectivity and accuracy still need improvement. Chromatographic methods and some electrochemical methods, while possessing high sensitivity, typically require specialized instruments and complex sample processing, which is not conducive to rapid detection and on-site analysis. Enzymatic detection usually utilizes an enzyme cascade reaction involving creatinine oxidase, creatine oxidase, and sarcosine oxidase to convert creatinine into hydrogen peroxide, which is then catalyzed by peroxidase to oxidize chromogenic substrates such as TMB, thereby achieving indirect detection of creatinine concentration. This type of method has the advantage of good selectivity, but natural peroxidases are essentially protein molecules, easily affected by temperature, pH, storage conditions, and coexisting components in the sample system, resulting in limited stability, high cost, and stringent storage requirements. Therefore, developing artificial nanozyme materials with peroxidase-like activity to replace natural peroxidase in constructing a creatinine colorimetric detection system is of great research significance.
[0004] Nanozymes are a class of nanomaterials with natural enzyme-mimicking activities, typically possessing advantages such as good structural stability, relatively simple preparation conditions, low cost, and ease of control. Among them, nanozymes with peroxidase-like activity can catalyze the oxidation of chromogenic substrates such as TMB to colored products in the presence of H₂O₂, making them suitable for constructing rapid and intuitive colorimetric detection systems. Layered double hydroxides are a class of two-dimensional layered materials composed of metal hydroxide plates and interlayer anions. They feature tunable metal composition, designable layered structure, exchangeable interlayer anions, and abundant surface active sites, showing potential application in peroxidase-like catalysis and colorimetric sensing. By adjusting the metal composition of the plates, the interlayer microenvironment, and the surface defect structure, it is hoped that the adsorption and activation capabilities of the materials for H₂O₂ and chromogenic substrates can be improved, thereby enhancing their catalytic performance.
[0005] Amino acids, as the basic building blocks of proteins, are closely related to life activities. Many amino acid residues are also catalytic active sites of natural enzymes, promoting substrate binding. Existing research shows that amino acid doping can enhance the POD-like activity of LDH nanozymes. However, the amount of amino acid doping is usually limited by its solubility and intercalation ability in LDH, and amino acid doping alone cannot achieve ideal catalytic performance. Although metal ions (such as Fe and Co) have been shown to enhance the catalytic activity of LDH, the use of metal ions or amino acid doping alone often fails to fully realize their synergistic effect, resulting in unsatisfactory catalytic activity and stability of the material in near-neutral environments, making it difficult to meet the sensitivity requirements of biosensoring. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing oxygen-vacancy-rich trimetallic layered hydroxides to solve the problems of insufficient metal component regulation, limited effective introduction of amino acids, inadequate oxygen defect construction, and insufficient ability to maintain peroxidase-like activity under weakly acidic to near-neutral conditions in the colorimetric detection of creatinine by existing LDH-type nanozymes.
[0007] This invention provides a method for preparing an oxygen-vacancy-rich trimetallic layered hydroxide, comprising the following steps: (1) Add La(NO3)3·6H2O, Ni(NO3)2·6H2O, Mn(NO3)2·6H2O, polyvinylpyrrolidone (PVP) and serine to deionized water and disperse by ultrasonication to obtain the first mixture; add urea to deionized water and disperse by ultrasonication to obtain the second mixture; (2) After the first mixture and the second mixture are mixed evenly, they are transferred to a reaction vessel for hydrothermal reaction to obtain the reaction product; (3) Centrifuge the reaction product obtained in step (2), collect the precipitate, and wash it three times with deionized water and ethanol respectively to remove unreacted raw materials and impurity ions; (4) The washed precipitate is dried in a vacuum oven to obtain a trimetallic layered hydroxide material, which is an oxygen-rich trimetallic layered hydroxide.
[0008] The serine is L-serine; the polyvinylpyrrolidone is PVP-K30.
[0009] Further, in step (1), the ratio of the amounts of La(NO3)3·6H2O, Ni(NO3)2·6H2O, Mn(NO3)2·6H2O, PVP, serine and deionized water in the first mixture is: 0.05-0.15mmol:1.0mmol:1.0mmol:0.2-0.5g:3-8mmol:40-60mL.
[0010] Furthermore, in step (1), the ratio of urea to deionized water in the second mixture is 1 mmol: 7-10 mL.
[0011] Further, in step (2), the volume ratio of the first mixture to the second mixture is 1:0.7-1.2.
[0012] Furthermore, in step (2), the conditions for hydrothermal treatment are: heating temperature of 120-160℃ and heating reaction time of 8-16h.
[0013] Furthermore, in step (4), the drying conditions are: drying temperature 60-80℃ and drying time 8-12h.
[0014] Another objective of this invention is to provide an oxygen-vacancy-rich trimetallic layered hydroxide material prepared by the above method. The trimetallic layered hydroxide has a layered double hydroxide structure, and the La, Ni, and Mn metal elements are uniformly distributed in the material. The surface of the trimetallic layered hydroxide has abundant oxygen vacancy defects, exhibiting an oxygen defect signal near g=2.003 in EPR testing, and displaying characteristic diffraction peaks of layered double hydroxides at 10-12° in XRD patterns. XPS testing of the trimetallic layered hydroxide shows a N atom percentage ≥4.0%.
[0015] The material exhibits peroxidase-like activity in a buffer system with pH 4.5-7.0, and can catalyze the oxidation of the chromogenic substrate TMB by hydrogen peroxide (H2O2) to generate a blue product.
[0016] Another objective of this invention is to provide an oxygen-rich vacancy trimetallic layered hydroxide prepared by the above method and its application in creatinine detection, for use in the preparation of creatinine detection reagents or kits.
[0017] The beneficial effects of this invention are as follows: (1) This invention addresses the problem that single amino acid doping or single metal regulation in existing LDH nanozymes is insufficient to fully enhance catalytic performance. By introducing La component, serine, and PVP into the Ni, Mn, and basal hydroxide system, multi-component synergistic regulation is achieved. Serine molecules contain functional groups such as carboxyl, amino, and hydroxyl groups, which can coordinate or complex with metal ions such as Ni, Mn, and La, regulating the hydrolysis, nucleation, and lamellar growth processes of metal ions. The introduction of La component helps to regulate the lamellar structure and local metal-oxygen coordination environment. PVP can improve the dispersion state of metal components and organic coordination molecules in the reaction system, reducing local enrichment and aggregation. The combined effect of these three components helps to overcome the limited effect of single amino acid doping or single metal regulation.
[0018] (2) The trimetallic layered hydroxide material prepared by this invention exhibits a strong oxygen vacancy signal, good peroxidase-like catalytic activity, and a wide pH range. ICP test results show that the La component can be effectively introduced into the NiMn layered hydroxide material; XPS test results show that a certain amount of N element exists in the material, indicating that serine and / or PVP-related nitrogen-containing components can participate in the material construction or exist stably; EPR test results show that the sample of Example 1 has the strongest oxygen vacancy signal near g=2.003, and its normalized relative oxygen vacancy intensity is 1.00, which is significantly higher than that of the comparative samples lacking serine, La component, or PVP. Furthermore, test results under different pH conditions show that the sample of Example 1 can still maintain 58.0% relative POD activity at pH 7.0, which is significantly higher than that of the comparative samples. The above results indicate that the synergistic effect of the La component, serine, and PVP is beneficial to the construction of oxygen vacancy sites and H2O2 activation, thereby improving the colorimetric catalytic efficiency in the TMB-H2O2 system and enhancing the material's ability to maintain catalytic activity under weakly acidic to near-neutral conditions.
[0019] (3) The oxygen-vacancy-rich trimetallic layered hydroxide material prepared by this invention can be used for sensitive colorimetric detection of creatinine. Under the action of creatininase, creatinease and sarcosine oxidase, creatinine generates H2O2 through a cascade reaction; the resulting H2O2 oxidizes TMB to generate blue oxTMB under the catalysis of the trimetallic layered hydroxide material of this invention, thereby realizing indirect colorimetric detection of creatinine concentration. The detection results show that the sample of Example 1 has a good linear response in the range of 1-150 μM when used for creatinine detection, with a detection limit of 0.68 μM; the detection limits of the samples of Example 2 and Example 3 are 0.86 μM and 0.76 μM, respectively, which are significantly lower than those of the comparative sample, indicating that the materials prepared within the limited formulation and process range of this invention have good colorimetric detection performance for creatinine. Attached Figure Description
[0020] Figure 1 The image shows the X-ray diffraction (XRD) pattern of Example 1. Figure 2 The image shows the scanning transmission electron microscope (STEM-EDS) image and elemental distribution (STEM-EDS mapping) of Example 1. Figure 3 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of Example 1. Figure 4 The image shown is an electron paramagnetic resonance (EPR) image from Example 1. Figure 5 The UV-Vis spectra of the samples from Example 1 and Comparative Examples 1-3 in the TMB-H2O2 system are shown. Figure 6 This is an absorbance curve of Example 1 at different creatinine concentrations; Figure 7 This is a linear standard curve of Example 1 applied to the colorimetric detection of creatinine concentration. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the scope of protection of the present invention is not limited thereto.
[0022] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meaning as commonly understood by those skilled in the art.
[0023] Example 1: (1) 0.1 mmol La(NO3)3·6H2O, 1 mmol Ni(NO3)2·6H2O and 1 mmol Mn(NO3)2·6H2O, 0.3 g PVP-K30 and 5 mmol L-serine were added to 50 mL of deionized water and ultrasonically dispersed for 1 h to obtain the first mixture; 5.5 mmol urea was added to 55 mL of deionized water and ultrasonically dispersed for 1 h to obtain the second mixture; (2) After the first mixture and the second mixture are mixed evenly, they are transferred to a polytetrafluoroethylene-lined reactor and placed in a 140°C oven for hydrothermal reaction for 12 hours to obtain the reaction product. (3) Centrifuge the reaction product obtained in step (2), collect the precipitate, and wash it three times with deionized water and ethanol respectively to remove unreacted raw materials and impurity ions; (4) The washed precipitate was dried in a vacuum oven at 70°C for 10 hours to obtain a trimetallic layered hydroxide material, which was recorded as the sample of Example 1.
[0024] Example 2: (1) 0.05 mmol La(NO3)3·6H2O, 1 mmol Ni(NO3)2·6H2O and 1 mmol Mn(NO3)2·6H2O, 0.2 g PVP-K30 and 3 mmol L-serine were added to 40 mL of deionized water and ultrasonically dispersed for 1 h to obtain the first mixture; 4 mmol urea was added to 28 mL of deionized water and ultrasonically dispersed for 1 h to obtain the second mixture; (2) After the first mixture and the second mixture are mixed evenly, they are transferred to a polytetrafluoroethylene-lined reactor and placed in a 120°C oven for hydrothermal reaction for 16 hours to obtain the reaction product; (3) Centrifuge the reaction product obtained in step (2), collect the precipitate, and wash it three times with deionized water and ethanol respectively to remove unreacted raw materials and impurity ions; (4) The washed precipitate was dried in a vacuum oven at 60°C for 12 hours to obtain a trimetallic layered hydroxide material, which was recorded as the sample of Example 2.
[0025] Example 3: (1) 0.15 mmol La(NO3)3·6H2O, 1 mmol Ni(NO3)2·6H2O and 1 mmol Mn(NO3)2·6H2O, 0.5 g PVP-K30 and 8 mmol L-serine were added to 60 mL of deionized water and ultrasonically dispersed for 1 h to obtain the first mixture; 10 mmol urea was added to 72 mL of deionized water and ultrasonically dispersed for 1 h to obtain the second mixture; (2) After the first mixture and the second mixture are mixed evenly, they are transferred to a polytetrafluoroethylene-lined reactor and placed in a 160°C oven for hydrothermal reaction for 8 hours to obtain the reaction product; (3) Centrifuge the reaction product obtained in step (2), collect the precipitate, and wash it three times with deionized water and ethanol respectively to remove unreacted raw materials and impurity ions; (4) The washed precipitate was dried in a vacuum oven at 80°C for 8 hours to obtain a trimetallic layered hydroxide material, which was recorded as the sample of Example 3.
[0026] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that no serine was added in step (1), while the other preparation conditions were the same as in Example 1.
[0027] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that La(NO3)3·6H2O was not added in step (1), while the other preparation conditions were the same as in Example 1.
[0028] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that no PVP was added in step (1), while the other preparation conditions were the same as in Example 1.
[0029] Application Example 1: POD Activity Test: The samples from the examples and comparative examples were dispersed in deionized water to prepare nanozyme suspensions with a concentration of 2 mg / mL. TMB and H2O2 solutions were also prepared, with TMB concentrations of 1 mM and H2O2 concentrations of 10 mM, respectively. 10 μL of nanozyme suspension, 10 μL of H2O2 solution, and 10 μL of TMB solution were added to 2970 μL of sodium acetate-acetic acid buffer (0.2 M, pH 4.5) and mixed thoroughly. The resulting mixture was incubated at room temperature for 20 min, and then the absorbance of the reaction solution was measured at 652 nm using a UV-Vis spectrophotometer to evaluate the peroxidase-like catalytic activity of each sample.
[0030] To further evaluate the POD catalytic adaptability of the samples under different pH conditions, the above reaction system was used, and the pH of the reaction system was adjusted to 4.5, 5.5, 6.5 and 7.0 respectively using buffer solutions of the corresponding pH values. The absorbance of the sample in Example 1 and the samples in Comparative Examples 1-3 was measured at 652 nm, and the relative POD activity of different samples under different pH conditions was calculated with the absorbance of each sample at pH 4.5 as 100%.
[0031] Application Example 2: Colorimetric Detection of Creatinine: Nanozyme suspensions, creatinine enzyme solutions, creatine kinase solutions, sarcosine oxidase solutions, TMB solutions, and creatinine standard solutions of different concentrations were prepared using deionized water for the examples and comparative samples. The concentrations were as follows: nanozyme suspension 2 mg / mL, creatinine enzyme solution 0.2 mg / mL, creatine kinase solution 0.1 mg / mL, sarcosine oxidase solution 0.2 mg / mL, and TMB solution 1 mM. The addition of different concentrations of creatinine standard solutions resulted in creatinine concentrations of 0, 0.05, 1, 3, 5, 10, 20, 50, and 150 μM in the detection system. 80 μL of PBS buffer, 10 μL of creatinine enzyme solution, 10 μL of creatine oxidase solution, 10 μL of sarcosine oxidase solution, and 20 μL of creatinine standard solutions of different concentrations were mixed. The PBS buffer concentration was 0.015 M, pH 7.5, and the mixture was incubated at 37 °C for 30 min to allow creatinine to generate H₂O₂ through an enzyme cascade reaction. Subsequently, 2850 μL of sodium acetate-acetic acid buffer, 10 μL of nanozyme suspension, and 10 μL of TMB solution were added to the above reaction system. The sodium acetate-acetic acid buffer concentration was 0.2 M, pH 4.5. The resulting mixture was incubated at room temperature for 20 min, and then the absorbance of the reaction solution was measured at 652 nm using a UV-Vis spectrophotometer for colorimetric quantitative analysis of creatinine.
[0032] Results and Analysis: Figure 1 The XRD pattern of the sample from Example 1 shows typical characteristic diffraction peaks of layered double hydroxide (LDH) materials in the low-angle region (10-12°), while diffraction peaks corresponding to the layered structure are observed in the mid-to-high-angle region (20-70°). These peak positions are similar to the main diffraction characteristics of NiMn-LDH and NiLa-LDH materials reported by Sivaraman and Jiang (Microchimica Acta, 2025, 192, 142 and Journal of Energy Chemistry, 2019, 33, 125-129). These results indicate that the obtained sample possesses the structural characteristics of NiMnLa-LDH type layered hydroxides. No obvious characteristic peaks of La2O3, La(OH)3, or other independent lanthanide impurities were observed in the spectrum, indicating that the La component does not form a distinct independent crystalline phase, but rather mainly participates in the construction of the layered hydroxide structure or exists in a highly dispersed state within the material.
[0033] Figure 2The image shows the TEM-EDS mapping of the sample from Example 1. As can be seen from the image, the sample from Example 1 exhibits a lamellar morphology with interlacing layers forming an open structure. The Ni, Mn, La, and O elements are relatively uniformly distributed in the sample area. No obvious local agglomeration or independent enrichment region of La element was observed, indicating that the method of the present invention is beneficial for forming trimetallic layered hydroxide materials with uniform elements and relatively complete layered structures.
[0034] Figure 3 The XPS test results for the sample of Example 1 show the characteristic signals corresponding to Ni, Mn, and La, further confirming the presence of these elements in the sample. The Ni, Mn, and La signals indicate that the three metal components can coexist in the resulting layered hydroxide material. Further ICP-MS testing of the Example 1 sample yielded results shown in Table 1. Table 1 shows that the relative molar ratio of La, Mn, and Ni in the Example 1 sample is 0.08:1:1.08, indicating that all three metal components (Ni, Mn, and La) can be effectively introduced into the resulting layered hydroxide material. Compared to the initial feed ratio of La:Mn:Ni = 0.10:1:1, the relative proportion of La in the product is slightly lower, indicating that although the La component can be effectively introduced into the NiMn layered hydroxide, its effective introduction amount is affected by the La content. 3+ The influence of ionic radius, coordination environment, and laminar structure matching was investigated. XPS analysis showed that the percentage of nitrogen atoms in the Example 1 sample was 4.2%, significantly higher than the comparative sample, indicating that the synergistic effect of appropriate amounts of La component, serine, and PVP contributes to the effective introduction and stable presence of nitrogen-containing organic components.
[0035] Figure 4 The EPR curve of the sample from Example 1 shows a significant oxygen defect signal near g=2.003, indicating the presence of oxygen defect-related unpaired electrons in the material. Combined with the statistical results of the relative intensity of oxygen defects in EPR curves in Table 1, the normalized relative intensity of oxygen defects in the sample from Example 1 is 1.00; the values for Comparative Examples 1, 2, and 3 are reduced to 0.56, 0.43, and 0.62, respectively. These results indicate that the absence of serine, the La component, or PVP weakens the formation ability of oxygen defects, with the absence of the La component resulting in the most significant decrease in the oxygen defect signal. This suggests that the synergistic effect of the La component, serine, and PVP is beneficial for constructing more oxygen defect sites in NiMn-based basal hydroxides, thus providing a structural basis for H2O2 activation and improved catalytic performance of POD-like materials.
[0036] Table 1. ICP metal atomic ratio, XPS N element content, and EPR oxygen defect intensity of Examples 1 and Comparative Examples 1-3
[0037] Following the method in Application Example 1, POD-like activity tests were performed on the samples from the examples and comparative examples. The test results are shown in […]. Figure 5 And Table 2. (As shown in Table 2) Figure 5 As shown, the TMB oxidation product oxTMB has a characteristic absorption peak at 652 nm, and the absorbance at this position can be used to evaluate the peroxidase-like catalytic activity of the material. The sample in Example 1 exhibits the highest absorption peak intensity at 652 nm, indicating that it possesses optimal POD-like catalytic performance. In contrast, the absorption peak intensities at 652 nm of the samples in Comparative Examples 1, 2, and 3 are all significantly reduced, indicating that the absence of serine, La components, or PVP all decreases the peroxidase-like catalytic activity of the resulting materials.
[0038] Further analysis of Table 2 shows that the relative intensity of POD activity was calculated by normalizing the absorbance of the sample from Example 1 at 652 nm under pH 4.5 conditions to 1.00. The relative intensities of POD activity for the samples from Examples 2 and 3 were 0.88 and 0.93, respectively, indicating that the samples prepared under the boundary conditions still possessed good POD-like catalytic activity, but lower than that of Example 1. The relative intensities of POD activity for Comparative Examples 1, 2, and 3 decreased to 0.50, 0.38, and 0.63, respectively, all significantly lower than those of the Example samples. These results demonstrate that the present invention can effectively improve the colorimetric catalytic ability of trimetallic layered hydroxide materials through the synergistic regulation of the La component, serine, and PVP.
[0039] To further evaluate the catalytic adaptability of the material under different reaction environments, the relative POD activities of the samples from Example 1 and Comparative Examples 1-3 under different pH conditions were tested according to the method of Application Example 1. The results are shown in Table 2. Table 2 shows that, when normalized to 100% absorbance at pH 4.5, the relative POD activities of the sample from Example 1 at pH 5.5, 6.5, and 7.0 were 92.0%, 77.5%, and 58.0%, respectively, indicating that it still maintains good catalytic activity under weakly acidic to near-neutral conditions. In contrast, the relative POD activities of the samples from Comparative Examples 1, 2, and 3 at pH 7.0 were only 29.5%, 23.8%, and 34.2%, respectively, significantly lower than those of the sample from Example 1. The above results indicate that the lack of serine, La component, or PVP significantly reduces the ability of the obtained material to retain POD-like activity under near-neutral conditions; while the sample of Example 1 of this invention still has a good catalytic response over a wide pH range, indicating that the synergistic effect of La component, serine, and PVP not only helps to improve the POD-like activity of the material, but also helps to broaden its pH applicable range.
[0040] Table 2. Results of POD activity, pH adaptability, and creatinine colorimetric assay for Examples 1-3 and Comparative Examples 1-3.
[0041] Following the method in Application Example 2, creatinine was measured in the sample from Example 1 using colorimetric assay. The test results are shown below. Figure 6 and Figure 7 .like Figure 6 As shown, the absorbance of the reaction solution at 652 nm gradually increased with the increase of creatinine concentration from 0.05 μM to 150 μM, indicating that creatinine produces H2O2 through a cascade reaction of creatinine oxidase, creatine enzyme, and sarcosine oxidase. The resulting H2O2 can oxidize TMB to oxTMB under the catalysis of the sample from Example 1. This result indicates that the sample from Example 1 can be used as a peroxidase-like catalytic material in a creatinine enzyme cascade colorimetric system to achieve indirect colorimetric detection of creatinine concentration.
[0042] Depend on Figure 7 It can be seen that within the creatinine concentration range of 1-150 μM, the absorbance at 652 nm shows a good linear relationship with the creatinine concentration, with the linear equation being y = 0.00146x + 0.0209 and the correlation coefficient R. 2 =0.997, and the detection limit is 0.68 μM. These results indicate that the sample from Example 1 exhibits a wide linear detection range and a low detection limit when used for creatinine detection, meeting the requirements for sensitive colorimetric detection of creatinine. The detection limit was calculated by dividing the standard deviation of the blank sample by three times the standard deviation and the slope of the standard curve.
[0043] Further tests were conducted on the POD-like activity and creatinine colorimetric detection performance of the samples from Examples 2, 3, and Comparative Examples 1-3. The results are shown in Table 2. Table 2 shows that the detection limits for creatinine colorimetric detection of the samples from Examples 2 and 3 were 0.86 μM and 0.76 μM, respectively, indicating that a trimetallic layered hydroxide material with good creatinine detection performance can still be obtained under the formulation and process boundary conditions defined in this invention. In contrast, the creatinine detection limits of the samples from Comparative Examples 1, 2, and 3 increased to 1.72 μM, 2.18 μM, and 1.55 μM, respectively, all significantly higher than those of the Example samples. Combined with the EPR oxygen vacancy relative intensity results in Table 1, it can be seen that the sample from Example 1 has the highest oxygen vacancy relative intensity and the best POD-like catalytic performance, while the oxygen vacancy intensity, POD-like catalytic activity, and creatinine detection performance of each comparative example sample decreased to varying degrees. The above results indicate that serine, La component and PVP are key regulatory factors in the technical solution of this invention. The absence of any one of these components will weaken the oxygen defect construction and H2O2 activation ability, thereby leading to a decrease in POD-like catalytic activity and an increase in the creatinine detection limit.
Claims
1. A method for preparing a trimetallic layered hydroxide rich in oxygen vacancies, characterized in that, Includes the following steps: (1) Add La(NO3)3·6H2O, Ni(NO3)2·6H2O, Mn(NO3)2·6H2O, polyvinylpyrrolidone and L-serine to deionized water and disperse by ultrasonication to obtain the first mixture; add urea to deionized water and disperse by ultrasonication to obtain the second mixture; (2) After the first mixture and the second mixture are mixed evenly, they are transferred to a reaction vessel for hydrothermal reaction to obtain the reaction product; (3) Centrifuge the reaction product obtained in step (2), collect the precipitate, and wash it with deionized water and ethanol respectively; (4) The washed precipitate is vacuum dried to obtain a trimetallic layered hydroxide material, which is an oxygen-rich trimetallic layered hydroxide. In step (1), the ratio of the amounts of La(NO3)3·6H2O, Ni(NO3)2·6H2O, Mn(NO3)2·6H2O, polyvinylpyrrolidone, L-serine and deionized water in the first mixture is: 0.05-0.15mmol:1.0mmol:1.0mmol:0.2-0.5g:3-8mmol:40-60mL.
2. The preparation method according to claim 1, characterized in that, In step (1), the ratio of urea to deionized water in the second mixture is 1 mmol: 7-10 mL.
3. The preparation method according to claim 1, characterized in that, In step (2), the volume ratio of the first mixture to the second mixture is 1:0.7-1.
2.
4. The preparation method according to claim 1, characterized in that, In step (2), the hydrothermal reaction conditions are: temperature 120-160℃, time 8-16h.
5. The preparation method according to claim 1, characterized in that, In step (4), the drying conditions are: temperature 60-80℃, time 8-12h.
6. An oxygen-vacancy-rich trimetallic layered hydroxide prepared by the preparation method according to any one of claims 1-5.
7. A trimetallic layered hydroxide with oxygen-vacancy enrichment according to claim 6, characterized in that, The three metal elements La, Ni, and Mn are evenly distributed in the trimetallic layered hydroxide; oxygen defect signals are present near g=2.003 in EPR testing, and characteristic diffraction peaks of layered double hydroxides are present at 10-12° in the XRD pattern; the percentage of N atoms in the XPS test of the trimetallic layered hydroxide is ≥4.0%.
8. The use of the oxygen-vacancy-rich trimetallic layered hydroxide of claim 7 in the preparation of creatinine detection reagents or kits.
Citation Information
Patent Citations
Composite oxide adsorbent for adsorption of medium / high temperature CO2
CN103785347A
Method for preparing flue gas desulfurizer by ball-milling recrystallization method and application of flue gas desulfurizer
CN120054188A
